Evaluating the GALAD Score in Diagnosing Hepatocellular Carcinoma - Cam Phuong, Pham; Trong Khoa, Mai; Thuan Loi, Nguyen; Thi Ly, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4DO - 10.25073/2588-1132/vnumps.4366, 2021)
This paper aims to evaluate the GALAD score in diagnosing hepatocellular carcinoma. The paper conducted a retrospective study of 86 Hepatocellular Carcinoma patients who underwent AFP, AFP-L3, and PIVKA II. The results show that the average age of the patients was 57.7 ± 11.14, the ratio of male/female was 11.34/1. The median values of AFP, AFP-L3, and PIVKA-II before treatment were 196 ng/mL, 16.2%, and 3154.5 mAU/mL, respectively. The sensitivity of AFP, AFP-L3, and PIVKA-II was 80.2%; 58.1%; and 88.4%, respectively. The combination of the three markers also showed a high sensitivity of 94.2%. The mean value of GALAD in the patients was 5.83 ± 5.3. The liver cancer probability index was 0.8485 ± 0.276. Overall, the paper results suggest that using the BALAD score is both easy to practice and economical, which is highly useful for the early detection of hepatocellular carcinoma. Keywords: Hepatocellular carcinoma, PIVKA-II, GALAD score. References [1] H. Sung, J. Ferlay, M. E. Rebecca, L. Siegel et al., Global Cancer Statistics 2020: GLOBOCAN Estimates of Incidence and Mortality Worldwide for 36 Cancers in 185 Countries, CA: aA Cancer Journal For Clinicians, 2021. [2] M. Makuuchi et al., Development of Evidence‐based Clinical Guidelines for the Diagnosis and Treatment of Hepatocellular Carcinoma in Japan Hepatology Research, Vol. 38, No. 1, 2008, pp. 37-51. 7 [3] M. Makuuchi, Clinical Practice Guidelines for Hepatocellular Carcinoma-the Japan Society of Hepatology 2009 update, Hepatol Res, Vol. 40, No. 1, 2010, pp. 2-144. [4] G. M. N. O. Wongjarupong, N. R. Chaiteerakij et al., Model Combining Pre-transplant Tumor Biomarkers and Tumor Size Shows More Utility Iin Predicting Hepatocellular Carcinoma Recurrence and Survival than the BALAD Models, World Journal of Gastroenterology, Vol. 24, No. 12, 2018, pp. 1321-1331. [5] L. R. Roberts, Current Status of the GALAD and BALAD Biomarker Models for Hepatocellular Carcinoma, Gastroenterology & Hepatology, Vol. 15, No. 12, 2019, pp. 672-675. [6] L.N. Khue, M.T. Khoa at el 2020, Guideline about Diagnosis and Treatment some type of Cancer, Ministry of Health, 2020, pp. 900-935. [7] National Comprehensive Cancer Network, Hepatocellular Carcinoma, 2020. [8] J. D. Yang, B. D. Addissie, K. C. Mara et al., GALAD Score for Hepatocellular Carcinoma Detection in Comparison with Liver Ultrasound and Proposal of GALADUS Score, Cancer Epidemiol Biomarkers Prev, Vol. 28, No. 3, 2019, pp. 531-538. [9] T. T. Ngoc, Studying the Role of Alpha-fetoprotein, Alpha-fetoprotein-L3 and Des-gamma-carboxy Prothrombin in Diagnosis and Treatment Of Hepatocellular Carcinoma, Thesis of PhD, Hanoi Medical University, 2020. [10] G. P. Caviglia, M. L. Abate, E. Petrini et al., Highly Sensitive Alpha-fetoprotein, Lens Culinaris Agglutinin-reactive Fraction of Alpha-fetoprotein and Des-gamma-carboxyprothrombin for Hepatocellular Carcinoma Detection, Hepatol Res, Vol. 46, No. 3, 2016, pp. E130-E135. [11] S. Berhane, H. Toyoda, T. Tada et al., Role of the GALAD and BALAD-2 Serologic Models in Diagnosis of Hepatocellular Carcinoma and Prediction of Survival in Patients, Vol. 14, No. 6, 2016, pp. 875-886. e6. [12] J. Best, L. P. Bechmann, J. P. Sowa et al., GALAD Score Detects Early Hepatocellular Carcinoma in an International Cohort of Patients with Nonalcoholic Steatohepatitis, Clin Gastroenterol Hepatol, Vol. 18, No. 3, 2020, pp. 728-735.e4.